The effect of density in larval rearing of the pullet carpet shell Venerupis corrugata (Gmelin, 1791) in a recirculating aquaculture system - Joaquim, Sandra (2017)
The pullet carpet shell Venerupis corrugata is an economically valuable species in several European countries, however, nowadays stocks are under high fishing pressure. Hatchery production of juveniles for release is a major contributor to strengthen the stock and consequently improve the sustainability of the natural stocks. This study aimed to determine the feasibility of rearing V. corrugata larvae with different larval densities (10, 40 and 200 larvae per mL) in a recirculating aquaculture system (RAS), compared with the traditional larval rearing methodology (Batch). The mean survival, growth and metamorphic rate of V. corrugata larvae in RAS was higher (11.1%; 71.3m; 21.6% respectively) than in the Batch system, in all tested densities. The larval growth was not affected by the initial density until 40 larvae per mL, however, 200 larvae per mL decreased the larval growth in length nearly 54m. The larval rearing time was shortened in 2days in the RAS system. The physical, chemical and microbiologic parameters suggested that the tested densities were not excessive to disturb the biofilter stability of RAS. The V. corrugata larval rearing performed at high larval stocking densities in RAS system present a reduction in the operating costs to produce this species.